2017
DOI: 10.1371/journal.ppat.1006561
|View full text |Cite
|
Sign up to set email alerts
|

A parapoxviral virion protein inhibits NF-κB signaling early in infection

Abstract: Poxviruses have evolved unique proteins and mechanisms to counteract the nuclear factor κB (NF-κB) signaling pathway, which is an essential regulatory pathway of host innate immune responses. Here, we describe a NF-κB inhibitory virion protein of orf virus (ORFV), ORFV073, which functions very early in infected cells. Infection with ORFV073 gene deletion virus (OV-IA82Δ073) led to increased accumulation of NF-κB essential modulator (NEMO), marked phosphorylation of IκB kinase (IKK) subunits IKKα and IKKβ, IκBα… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 53 publications
(87 reference statements)
0
28
0
1
Order By: Relevance
“…ICAM‐1 expression is regulated by the NF‐κB pathway . ORFV encodes at least five NF‐κB inhibitors, which can block NF‐κB signalling . Thus, blocking of ICAM‐1 expression by ORFV on its host cell may be linked to a successful inhibition of the NF‐κB pathway in infected KC and FB.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM‐1 expression is regulated by the NF‐κB pathway . ORFV encodes at least five NF‐κB inhibitors, which can block NF‐κB signalling . Thus, blocking of ICAM‐1 expression by ORFV on its host cell may be linked to a successful inhibition of the NF‐κB pathway in infected KC and FB.…”
Section: Discussionmentioning
confidence: 99%
“…ORFV exerts its effects through encoding novel inhibitors to subvert the pro‐inflammatory NF‐κB signaling pathway, a crucial regulator of host innate immune response. The ORFV 002, 024, 073, 119, and 121 genes have been reported to play roles in NF‐κB pathway regulation …”
Section: Orfv and Immune Escapementioning
confidence: 99%
“…The gene expression profiles of ovine fetal turbinate cells infected with OV‐IA82Δ073 were analyzed by microarray assay. The results showed that the expression of chemokines and other pro‐inflammatory genes was significantly increased in cells infected with IA82Δ073 (IA82 strain with ORFV073 gene deletion), and most of the gene expression changes were regulated by the NF‐κB transcription factor family . ORFV073 affected neither the phosphorylation of p65 in the cytoplasm nor the nuclear transfer of p65, further suggesting that ORFV073 was located in the nucleus when inhibiting NF‐κB signal transduction.…”
Section: Orfv and Immune Escapementioning
confidence: 99%
See 2 more Smart Citations